2020
DOI: 10.3390/ijms21197287
|View full text |Cite
|
Sign up to set email alerts
|

MiRNAs as Noninvasive Biomarkers and Therapeutic Agents of Pituitary Adenomas

Abstract: Pituitary adenoma (PA) accounts for 10–15% of all intracranial neoplasms. Even though most pituitary adenomas are benign, it is known that almost 35% of them exhibit an aggressive clinical course, including rapid proliferative activity and invasion of neighboring tissues. MicroRNAs (miRNAs) are short single-stranded RNA molecules that can influence post-transcriptional regulation by controlling target genes. Based on research data on miRNAs over the past 20 years, more than 60% of genes encoding human proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 81 publications
0
32
0
2
Order By: Relevance
“…According to reports, p38MAPK can promote the migration and metastasis of BRAF mutant melanoma by inducing PMCA4 degradation. [11] PMCA2 is enriched in basal breast cancer. Silencing PMCA2 can reduce the proliferation of breast cancer cells, thereby silencing the isoforms PMCA1 and PMCA4.…”
Section: Discussionmentioning
confidence: 99%
“…According to reports, p38MAPK can promote the migration and metastasis of BRAF mutant melanoma by inducing PMCA4 degradation. [11] PMCA2 is enriched in basal breast cancer. Silencing PMCA2 can reduce the proliferation of breast cancer cells, thereby silencing the isoforms PMCA1 and PMCA4.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, repeated surgery and sampling in order to define the real molecular profile of the tumor progression is not always possible. Liquid biopsy is a real-time sampling of biomarkers from biofluids such as ncRNAs [ 37 , 38 ]. Liquid biopsy appears as a promising approach to non-invasive detection, molecularly characterized, and monitoring central nervous system (CNS) tumors progression and invasive PAs in particular.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the development of new screening methods, including the detection of molecular biomarkers of early stages of tumorigenesis, is of great importance. In this scenario, it is reasonable to assume that tumor progression will increase the expression level of certain oncogenic circulating ncRNAs, for example, in the bloodstream, in patients with invasive PA [ 37 , 38 ]. As a result, circulating miR-200a and lncRNA ANRIL are becoming candidates of emerging non-invasive biomarkers for invasive PA.…”
Section: Discussionmentioning
confidence: 99%
“…Palumbo et al identified 17 miRNAs to be differentially expressed in GH-producing pituitary tumors; however, none were encoded at 14q32 [ 138 ]. Pituitary tumor-transforming 1 ( PTTG1 ) was identified as a target of miR-126 and miR-381 encoded at 14q32 cluster [ 139 ]. Also, Liang et al demonstrated that overexpression of 4 14q32 miRNAs (miR-655, miR-300, miR-381 and miR-329) inhibited proliferation, migration and invasion, but induced apoptosis in GH3 and MMQ rat pituitary cells and regulated the PTTG1 expression [ 90 ].…”
Section: Mirnas In Endocrine Tumorsmentioning
confidence: 99%